2014
DOI: 10.1016/j.ica.2014.08.011
|View full text |Cite
|
Sign up to set email alerts
|

X-ray photoelectron spectroscopy of transition metal ions attached to the surface of rod-shape anatase TiO2 nanocrystals

Abstract: X-ray photoelectron spectra were obtained for a series of M-TiO 2 samples in which transition metal ions are directly attached to the surface of anatase TiO 2 nanocrystals. The samples were prepared using CrCl 3 .nH 2 O, MnCl 2 .nH 2 O, FeCl 2 .nH 2 O, CoCl 2 .nH 2 O, NiCl 2 .nH 2 O, and CuCl 2 .nH 2 O as metal sources. We observed spontaneous air oxidation of the metal for the Mn-TiO 2 and Fe-TiO 2 samples as indicated by rapid color changes. X-ray photoelectron spectroscopy (XPS) data confirms the oxidation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 56 publications
(56 reference statements)
3
18
0
Order By: Relevance
“…In our previous XPS studies of Co (surface) -TiO 2 and M,M 0 (surface) -TiO 2 we observed Co 2p 3/2 binding energies of 780.5-780.9 eV. 37,43 Based on the new XPS data, it is apparent that the Co 2p 3/2 binding energy for Co (doped) -TiO 2 is approximately 1 eV larger than for Co (surface) -TiO 2 . Choudhury et al report binding energies of 781.4 eV and 797.2 eV for Co 2p 3/2 and 2p 1/2 electrons from XPS study of Co 2+ doped TiO 2 nanoparticles.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 76%
“…In our previous XPS studies of Co (surface) -TiO 2 and M,M 0 (surface) -TiO 2 we observed Co 2p 3/2 binding energies of 780.5-780.9 eV. 37,43 Based on the new XPS data, it is apparent that the Co 2p 3/2 binding energy for Co (doped) -TiO 2 is approximately 1 eV larger than for Co (surface) -TiO 2 . Choudhury et al report binding energies of 781.4 eV and 797.2 eV for Co 2p 3/2 and 2p 1/2 electrons from XPS study of Co 2+ doped TiO 2 nanoparticles.…”
Section: X-ray Photoelectron Spectroscopymentioning
confidence: 76%
“…It has been discussed that the ratio between the two peaks can be correlated to the surface area of the material [30]. In Figure 1 (e), the titanium atom shows two distinct peaks at 458.4 eV for the Ti2p1/2 and at 459.2 eV for the Ti2p3/2 showing the clear evidence of the element present in the surface of the Ppy-CS-TiO2 nanocomposite films [31]. FE-SEM micrographs confirmed the homogeneous distribution of TiO2 at the surface of the Ppy-CS-TiO2 nanocomposites films in Figure 2 (a), which shows the white dots in colour of the nanoparticles of TiO2.…”
Section: Resultsmentioning
confidence: 91%
“…species and the feature at 712.57 eV may be able to attribute to Fe 3? [31][32][33][34][35]. The XPS peak at 717.57 eV may be attributed to the satellite Fe 2?…”
Section: Resultsmentioning
confidence: 99%